AB0024 WHOLE BLOOD ENDOGENOUS RETROELEMENT ACTIVITY ASSOCIATES WITH ANTI-CCP TITRES IN EARLY DRUG NAïVE RA AND IS PREFERENTIALLY INCREASED IN CD5+ AND NAïVE B CELLS. (June 2019) - Cooles, Faye; Pedrola, Gemma Vidal; Anderson, Amy; Naamane, Najib; Skelton, Andrew; Pratt, Arthur; Hilkens, Catharien; Shukla, Ruchi; Isaacs, John
Abstract : Background: Endogenous retroelements of which LINE1, Alu and LTR are the main subsets, constitute approximately 50% of the human genome. They are mobile genetic elements derived from the historical genomic integration of retroviruses. Whilst most are inactive, some expression of viral mRNA and subsequent protein is retained. This theoretically could promote immune activation, for example by triggering type 1 interferon (IFN-I) production and notably Alu has been identified as a target for Ro60 autoantibody. Retroelements may therefore provide a mechanism whereby tolerance is breached in autoimmunity. Objectives: To examine the potential clinical impact of retroelement activity in early drug naïve rheumatoid arthritis (eRA). This stage of disease was chosen to minimise therapeutic confounding. Methods: Drug-naïve eRA and healthy controls (HC) were recruited and clinical characteristics including disease activity, immunoglobulins (IgA, IgG, IgM), ESR, CRP, rheumatoid factor (RF) and anti-cyclic citrullinated peptide (anti-CCP) autoantibody titres documented. Serum cytokines (IFN-γ, IL-6, IL-12 p70, TNF-α, IL-1β, IL-2, IL-13, IL-4, IL-10) were also measured. Whole blood (WB) RNA was extracted and expression of an IFN-I gene signature (IGS: MxA, IFI6, OAS1, ISG15, IFI44L ) and LINE1 5'UTR activity quantified using RT-PCR. In addition anti-CCP and RF positive (double seropositive) eRA peripheral blood plasmacytoid dendritic cells (pDCs), myeloid DCs, CD19 + B cells, monocytes, CD4 + and CD8 + T cells were flow cytometrically sorted. CD19 + B cell subsets were further sorted from double seropositive eRA and disease controls (early, drug naïve, psoriatic arthritis, PsA) into CD5 + B cells, age associated B cells (CD19 hi CD11c + CD21 - ), naïve (IgD + CD27 - ) and memory (IgD - CD27 + ) B cells. Cell specific expression of LINE1, Alu and LTR was quantified by NanoString nCounter and analysed using R Core Team (2013). WB RNA analysis for continuous and categorical variables included linear regression and Mann-Whitney U tests respectively (GraphPad Prism, significance p<0.05). Results: WB LINE1 expression for 56 eRA patients (median age 58 [range 30-87], male:female 3:4, 77% seropositive for either RF or anti-CCP) and 23 HC (median age 39 [range 23-62], male:female 1:1) was obtained. WB LINE1 activity was not associated with age or gender and was comparable between cohorts. However in eRA a unique, robust positive association between WB LINE1 and anti-CCP titres was identified (see table and figure). Additionally, when comparing eRA circulating cell subsets, B cells had the highest expression of Alu, LINE1 and LTR (n=8, median age 56 [range 49-64], male:female 1:1). Furthermore, there was significantly increased expression of all retroelement classes in eRA CD5+ and naïve B cells compared with PsA (n=4, male:female 1:1 and median age 62 for both with age range [63-78] and [60-80] respectively). Conclusion: This is the first time peripheral blood retroelement activity has been examined in both HC and RA. It highlights intriguing, IFN-I independent, associations between anti-CCP titres, autoantibody producing B cells (CD5+) and retroelements. We suggest retroelements may play a more extensive role in autoantibody generation and may ultimately provide a novel target in the treatment or prevention of RA. Disclosure of Interests: Faye Cooles: None declared, Gemma Vidal Pedrola: None declared, Amy Anderson: None declared, Najib Naamane: None declared, Andrew Skelton: None declared, Arthur Pratt Grant/research support from: Dr. Pratt is in receipt of an externally peer-reviewed Investigator Initiated Research grant from Pfizer (£66, 000)., Grant/research support from: Dr. Pratt is in receipt of an externally peer-reviewed Investigator Initiated Research grant from Pfizer (£66, 000)., Speakers bureau: Dr Pratt has received honoraria from Eli Lilly and Janssen-Cilag Ltd. for his time in preparing presentations for non-promotional meetings that have been paid directly to Newcastle University., Speakers bureau: Dr Pratt has received honoraria from Eli Lilly and Janssen-Cilag Ltd. for his time in preparing presentations for non-promotional meetings that have been paid directly to Newcastle University., Catharien Hilkens: None declared, Ruchi Shukla: None declared, John Isaacs Grant/research support from: Pfizer, Grant/research support from: Pfizer, Consultant for: Abbvie, Pfizer, Roche, Galvani, Merck, Gilead, Eli Lilly, Amgen, Janssen, Celltrion, NAPP, Consultant for: Abbvie, Pfizer, Roche, Galvani, Merck, Gilead, Eli Lilly, Amgen, Janssen, Celltrion, NAPP, Speakers bureau: Abbvie, Pfizer, Eli Lilly, Speakers bureau: Abbvie, Pfizer, Eli Lilly